A Review of The Impact of Coach Authority on Sports Emotions and Behavioral Responses - Zhang, Tingran; Zhang, Mufan; Yang, Yi; Luo, Jiong (Quality in Sport, 2024)
Most athletes have experienced negative anger when facing coach authority, but coach authority may also evoke positive emotions in athletes, as coach authority contains two layers of connotations: authoritarianism and strictness. This study explores the relationship between coach authority and athlete's emotional and behavioral tendencies based on Lazarus's emotional theory, elucidates the emotional changes of athletes facing coach authority, summarizes the theoretical framework and possible development process of coach authority and athlete's emotional and behavioral tendencies, and provides important references for the training skills and team management of sports coaches.